2020
DOI: 10.1515/reveh-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Human health risk assessment of heavy metals via consumption of fish from Kao Bay

Abstract: AbstractWater pollution by heavy metals due to discharge from gold mining activity has threatened the aquatic environment and human health of the community around Kao Bay. This report review explores the level of mercury and arsenic in the fish and the health risk of fish consumption within the community around Kao Bay. Fish from 10 spots in the bay were analyzed for mercury and arsenic using Atomic Absorption Spectrophotometry. Community members around Kao Bay were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…This study in fact shows that exposure to PM10 and PM2.5 will increase the risk of respiratory health disturbance and can induce formation of micronucleus among children who live near the site of industrial activity. A study in addition indicated that exposure to PM2.5 high concentrations increase the risk of both acute and chronic respiratory health problems of elementary school children who live near cement industry activity areas [1,[13][14][15] as particle PM2.5 exposure can lead to micronucleus formation in children.…”
Section: Discussionmentioning
confidence: 99%
“…This study in fact shows that exposure to PM10 and PM2.5 will increase the risk of respiratory health disturbance and can induce formation of micronucleus among children who live near the site of industrial activity. A study in addition indicated that exposure to PM2.5 high concentrations increase the risk of both acute and chronic respiratory health problems of elementary school children who live near cement industry activity areas [1,[13][14][15] as particle PM2.5 exposure can lead to micronucleus formation in children.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate resources will create a barrier to policy implementation [26][27][28][29][30] .outh life is a very decisive life for their next future life. The activities that have been carried out by youth counseling information center officers in South Buru District are (1) establish a counseling information center in the school environment to provide information services and counseling about 8 Family Functions, Marriage Age Maturity, TRIAD KRR, Life Skills, Gender, Advocacy and Communication information and education.…”
Section: Discussionmentioning
confidence: 99%
“…The THQ estimated the non-carcinogenic health risk of consumers due to the intake of heavy metal contaminated fish use an oral reference dose (RfD) of Hg, Pb, Cd, As, Ni [53,59]. The reference doses (mg/kgBW/day) defined as the maximum tolerable daily intake of a specific metal that does not result in any deleterious health effects (Hg = 0.0003; Pb = 0.004; Cd = 0.001; As = 0.0003; Ni = 0.02 mg/kg/day) [3,61,62]. When THQ < 1, there is a health benefit from fish consumption and the consumers are safe, whereas THQ > 1 suggests a high probability of adverse effects human health.…”
Section: Target Hazard Quotients (Thq)mentioning
confidence: 99%